Enhancing histology learning in sports science education through a functional approach and virtual microscopy practical sessions - Ambardini, Rachmah Laksmi; Arovah, Novita Intan; Indra, Eka Novita (Journal Sport Area, 2024)
Background Problems: Histology is a critical component of the sports science curriculum, as it thoroughly explains the connection between the structure and function of cells, tissues, and organs. Research Objective: This study investigates the improvement of histology learning among sports science students by employing a functional approach and practical sessions with virtual microscopy. Methods: The study adopted a quasi-experimental design with 103 students from the Sports Science program, enrolled in a histology course with two parallel classes. The students were divided into experimental (n = 56) and control groups (n = 46) using cluster random sampling based on their classes. The experimental group received instruction using virtual microscopy, while the control group was taught using light microscopy throughout the semester. Both groups were assessed on their learning outcomes at the end of the semester through a written exam. Experimental group students also provided feedback on the courses. Using the independent t-test, the learning outcomes were compared between groups. Students’ feedback was analysed descriptively. Findings and Results: The results revealed that the average test scores for participants in the experimental group were significantly higher than those in the control group (74.9 ± 7.8 and 68.9 ± 9.6, respectively). Student feedback indicated that the majority concurred that the functional approach to histology teaching enhanced their understanding of histological structures. They also noted that practical virtual microscopy sessions improved their comprehension of the topics studied. Additionally, nervous tissue was identified as the most challenging tissue to learn, primarily due to visualisation difficulties in relating microscopic and macroscopic structures and the abundance of new terminology to remember. Conclusion: The findings suggest that combining a functional approach with virtual microscopy notably enhances the quality of histology education, equipping sports science students with a comprehensive understanding and essential practical skills for their academic and professional development.